Agency-preserving robotic assistance for grasp slip recovery in body-powered prostheses - Davis, Benjamin; Abbott, Michael; Stuart, Hannah S. (Frontiers in Robotics and AI, 2025)
Existing studies demonstrate that performance in reaction-based tasks can be improved using external robotic assistance without reducing the user’s sense of agency, particularly when assistance is delivered near the user’s natural reaction time. This finding has promise for assistive technologies like upper limb prostheses, where agency contributes to long-term use and users’ natural slip reflexes are hindered by reduced feedback and proprioception. However, prior studies lack the physical feedback of device movement inherent to many assistive devices like body-powered prostheses or exoskeletons where user and device are physically coupled. In this work, we explore the relationship between robotic assistance, performance, and agency when such feedback is present. We study how the timing of robotic assistance alters performance and agency, as experienced through the feedback of a body-powered transmission. We collect data from twenty participants in a simulated slip reaction task using a custom body-powered prosthesis emulator, with robotic grasp assistance provided at various delays relative to the onset of slip. Results show that, as assistance becomes more aligned with reaction times, agency increases while performance benefits are still obtained, even if users are aware of the assistance and perceive an increase in performance. Our findings suggest that in scenarios where users can physically perceive robotic assistance and its benefits, such as in body-grounded assistive technologies like body-powered prostheses or exoskeletons, temporal alignment between the user and robotic assistance plays a role in both performance and user experience.